A "UNLOCKING THE POTENTIAL OF E-GOVERNMENT: EXPLORING DETERMINANTS OF USER INTENTION IN A SMALL ISLAND DEVELOPING STATE" - Gunnoo, Leenshya; Bindah, Eric (The journal of contemporary issues in business and government, 2024)
Efficient delivery of e-government services offers a wide array of benefits, including enhanced governmental efficiency and cost savings, heightened openness, and improved public engagement. This research aims to explore the factors influencing the perspectives of respondents about the elements that influence their desire to use eservices offered by the government. This study examines the primary determinants influencing the intention to utilise e-services provided by the government of Mauritius. The factors under study include perceived usefulness, perceived ease of use, perceived risk, and social influence. A total of 300 questionnaires were deemed suitable for analysis. The SPSS software was used to acquire a summary of demographics and to analyse the hypothesis. Through the use of quantitative analysis, a total of four independent variables were developed, including nine distinct features. These variables serve to elucidate the perspective of the respondents and establish the correlation between the independent variables and usage intention. Regarding the relationship between the variables, the findings indicate the presence of many statistically significant positive relationships between the dependent and independent variables. Nevertheless, a limited number of attributes exhibited no statistically significant link with the intention to use. Based on the findings of the study, appropriate suggestions were formulated to enhance the intention to use e-services offered by the government.